2020
DOI: 10.1021/acs.energyfuels.9b04352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hot Water-Based Extraction Process on the Removal of Petroleum Hydrocarbons from the Oil-Contaminated Soil

Abstract: The properties including oil content, density, high viscosity, and corresponding components were analyzed in the samples of the oil-contaminated soil from one country in the Middle East; also, chemical composition of the solids in the oil-contaminated soil was analyzed by using the X-ray deflection structure analysis method. Characterization results of obtained samples showed the similarities of the oil-contaminated soil with the Canadian oil sand, and then the hot water-based extraction technology that is suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Many studies have demonstrated that surfactants are promising cleaning agents, and satisfactory cleaning results can be obtained using cationic, anionic, and non-ionic surfactants; however, because of the negative charge of oily sludge particles, cationic surfactants tend to remain in the soil and have a substantial impact on the environment. Thus, anionic and non-ionic surfactants are usually used, which have been investigated to optimize the formulations of surfactants and investigate the washing and extraction effects of their single and combined use [78].…”
Section: Surfactantsmentioning
confidence: 99%
“…Many studies have demonstrated that surfactants are promising cleaning agents, and satisfactory cleaning results can be obtained using cationic, anionic, and non-ionic surfactants; however, because of the negative charge of oily sludge particles, cationic surfactants tend to remain in the soil and have a substantial impact on the environment. Thus, anionic and non-ionic surfactants are usually used, which have been investigated to optimize the formulations of surfactants and investigate the washing and extraction effects of their single and combined use [78].…”
Section: Surfactantsmentioning
confidence: 99%
“…31 Many studies have shown that the effects of compound cleaning agents are better than the cleaning effects of a single detergent. For example, Chen et al 32 studied the effect of compound surfactants, Tween 80, SDBS, and washing powder on the cleaning effect. The results confirmed that the cleaning effect of the composite surfactant group on the hot water leaching process of oil sludge and oily soil was significantly better than those of the other four groups.…”
Section: Compounding Of Cleaning Agentsmentioning
confidence: 99%
“…For instance, when oil sands were cleaned using water washing, the asphaltene was easily removed from the silica surface by the action of chemicals and fluid disruption. In contrast, asphaltenes on clay surfaces were difficult to remove [10]. The difference between properties of oil-silica and oil-clay interfaces is the fundamental reason for this variation [11].…”
Section: Introductionmentioning
confidence: 99%